How does growth mindset affect mental health of high school students during the COVID-19 epidemic? The role of grit and coping strategies - Zhang, Libin; Qi, Huan; Wang, Chenxu; Wang, Tian; Zhang, Yunyun (Frontiers in Psychiatry, 2022)
Background The outbreak of COVID-19 epidemic continues to unfold globally, which harms the public’s mental health. Adolescents’ mental health is affected by social isolation and lockdown during the COVID-19 epidemic. The implicit theory of thoughts-emotion-behavior states that individuals with a growth mindset believe that thoughts, emotions, and behaviors can be changed through effort and tend to persist in pursuing higher goals and maintain enthusiasm as well as cope with stress resiliently, thus having higher gritty and levels of mental health. This study aimed to explore the role of grit and coping strategies in the influence of the growth mindset on adolescents’ mental health during the COVID-19 epidemic period. Methods A total of 1564 participants (Mage = 17.02, 760 boys, 804 girls) from three high schools in China were recruited to complete The Self-report Questionnaire-20, The Growth Mindset Scale, The Short Grit Scale, and The Coping Style Scale to evaluate mental health, growth mindset, grit, and positive coping strategies, respectively. Results The results showed that growth mindset has no significant indirect effect on mental health through grit but has a significant indirect effect on mental health through coping strategies. The results of chain mediation analysis showed that grit and coping strategies play chain mediating roles between growth mindset and adolescents’ mental health. Conclusion The findings suggest that cultivating a growth mindset, developing grit, and teaching adolescents to adopt positive coping strategies can improve adolescents’ mental health.